Analisis Perilaku Hidup Bersih dan Sehat dalam Meningkatkan Kecerdasan Ekologis Siswa Sekolah Dasar - Sinta Maria; Harmawati; Yulistina Nur DS; Sri Wulan Anggraeni; Fahmi Rizal (Postgraduate, University of Mataram, 2024)
This study aims to determine clean and healthy living behavior in improving the ecological intelligence of Sukamerta 2 public elementary school students. The method used in this research is descriptive qualitative research. Data collection in this study used observation, interviews, questionnaires and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this study indicate that teachers have an important role in creating clean and healthy living behavior at school. Teachers are one of the figures modeled by students, so the driving factor in increasing students' ecological intelligence is the teacher. Based on the questionnaire results, it can be concluded that Sukamerta 2 State Elementary School students who practice clean and healthy living behavior are 45 students (64.29%), while those who do not practice clean and healthy living behavior are 25 students (35.71%). So it can be concluded that it is necessary to implement clean and healthy living behavior for all students and is in the good category so that the value of ecological intelligence of students on clean and healthy living behavior is normal or good and in order to create a better school environment in maintaining cleanliness and comfort in learning and teaching activities.